Lactobacillus delbrueckii Ameliorates Intestinal Integrity and Antioxidant Ability in Weaned Piglets after a Lipopolysaccharide Challenge - Chen, Fengming (Oxid Med Cell Longev, 2020)
This study was conducted to evaluate the effect of dietary supplementation with Lactobacillus delbrueckii (LAB) on intestinal morphology, barrier function, immune response, and antioxidant capacity in weaned piglets challenged with lipopolysaccharide (LPS). A total of 36 two-line crossbred (Landrace × large Yorkshire) weaned piglets (28 days old) were divided into three groups: (1) nonchallenged control (CON); (2) LPS-challenged control (LPS); and (3) LAB+LPS treatment (0.2% LAB+LPS). Compared to the LPS piglets, the LAB+LPS piglets improved intestinal morphology, indicated by greater (P < 0.05) villus height in the duodenum and ileum; villus height : crypt depth ratio in the duodenum, jejunum, and ileum, as well as decreased (P < 0.05) crypt depth in the jejunum and ileum; and better intestinal barrier function, indicated by upregulated (P < 0.05) mRNA expression of tight junction proteins in the intestinal mucosa. Moreover, compared to the LPS piglets, LAB significantly decreased (P < 0.05) concentrations of TNF-α and IL-1β in the small intestine and increased (P < 0.05) IL-10 levels in the jejunum and ileum. Additionally, LAB increased (P < 0.05) T-AOC activities of the colon, GSH concentrations of the jejunum, and mRNA expression of CAT and Cu/Zn-SOD, while reduced (P < 0.05) MDA concentrations in the jejunum and ileum in LPS-changed piglets. Collectively, our results indicate that supplementation of LAB improved intestinal integrity and immune response and alleviated intestinal oxidative damage in LPS-challenged piglets.